RECLAMATION OF IRRIGATED AGRICULTURE THROUGH TILE DRAINAGE AT FOURTH DRAINAGE PROJECT, FAISALABAD - A. H. Azhar; M.N. Bhutta; M. Latif (Journal of Animal and Plant Sciences, 2010)
Fourth Drainage Project (FDP) has been evaluated in terms of improvement in land and groundwater conditions. The investigations revealed that drainage project was capable of controlling watertable between the pipelines at a depth of 100 to 150 cm below the ground level. There was also an improvement in shallow water quality (from hazardous to usable) due to installation of drainage system. The pre-project percentage of area under useable class was 23% which increased to 35% during post-project period. Where as, the area under hazardous class decreased from 48% to 34% during the post-project period. Surface and profile salinity levels were also improved. Salt affected area representing surface salinity level, decreased from 42% to 22% during post-project period. Non-Saline Non-Sodic (NS-NS) area representing profile salinity level, increased from 50% to 64% during the post-project period. The cropping intensity increased from 102% to 157% due to project implementation. Hence, subsurface drainage project is performing well in FDP area of Punjab province. However, the benefits of project can further be enhanced by improving O&M facilities, capacity building of staff as well as credit facilities to the farmers.
Keywords: Reclamation; irrigated agriculture; tile drainage; fourth drainage project; waterlogging; salinity